The effect of heat treatment on the nutritional value and antioxidant activity of sulphur shelf (Laetiporus sulphureus) - Iwona Adamska; Katarzyna Felisiak (NFS Journal)
Thermal processing of mushrooms affects their taste and health-promoting properties. The study aimed to determine changes in the nutritional value and antioxidant activity of the Laetiporus sulphureus mushroom under the influence of thermal processing. Pieces of mushroom subjected to blanching, cooking, stewing and frying were examined. The nutritional value (moisture, protein, fat and ash content) and content of bioactive compounds were determined, the carbohydrate content and caloric value were calculated. Trolox equivalent antioxidant activity (TEAC), free DPPH radicals scavenging ability (RSA) and ferric reducing antioxidant power (FRAP) of fruiting bodies before and after thermal processing were determined. The type of processing significantly affected the content of water, fat, ash, carbohydrates, the caloric value of mushrooms and their antioxidant activity. Although fried mushrooms had the highest calorific value, they also had the highest carbohydrate content, high antioxidant activity and were assessed best in terms of sensory properties.